Constraints Perceived by the Farmers in Adoption of Improved Ginger Production Technology- a Study of Low Hills of Himachal Pradesh - Kumar, Sanjeev; Singh, S. P.; Sharma, Raj Rani (International Journal of Bio-resource and Stress Management, 2018)
The present study was conducted using multistage sampling technique in Jhandutta and Sadar blocks of Bilaspur district of Himachal Pradesh during 2016-17. A sample of 100 ginger growing farmers was collected by personal interview method through well-structured pre tested schedule. The results of the study revealed that in case of technological constraints major constraints faced by the farmers were lack of knowledge about high yielding varieties and lack of technical guidance with mean percent score (MPS) of 89 and 87. The major input supply constraints were worked out to be non-availability of improved high yielding varieties (MPS 84) and lack of processing facilities (MPS 82). Among the economic & marketing constraints, high fluctuations in market price (MPS 89) and high cost of inputs (MPS 84) were major constraints and in general constraints category, lack of resources followed by low risk bearing abilities of farmers were major constraints with MPS of 78 and 70, respectively. Overall, among all the major categories of constraints, technological constraints (MPS 77.86) were up to greatest extent followed by economic and marketing constraints (MPS 76.75), input supply constraints (MPS 75.00) and general constraints (MPS 59.67), which indicated the need of strengthening the research-extension farmer linkage, provision of cheap credit facilities, establishment of processing units as well as organized regulated markets for efficient production and marketing of ginger crop in the study area.